Gamma alumina as a saturable absorbing material for C- and L-band ultrafast mode-locked fiber lasers - Pikau, N. F.; Mohd Yusoff, N.; Sarmani, A. R.; Muhammad, F. D.; Alresheedi, M. T.; Ng, E. K.; Mahdi, M. A. (Elsevier B.V., 2024)
This work demonstrates femtosecond pulse generations in C- and L-band regimes utilizing a gamma-aluminum oxide/polydimethylsiloxane saturable absorber (γ-Al2O3/PDMS-SA) via mode-locking technique. The γ-Al2O3/PDMS-SA has a 7.3% modulation depth and a moderate saturation intensity of 303 MW/cm2, and estimated damage threshold of greater than 8.49 and 3.57 GW/cm2 pumping intensities in C- and L-band wavelengths, respectively. In the C-band laser cavity, the generated mode-locked pulse delivered a low threshold of 28.7 mW and an ultrafast width of 622 fs. Meanwhile, a higher threshold of 108.6 mW and 942 fs pulse width were measured in the L-band laser cavity centered at 1611 nm. These demonstrations showcase a versatile feature of γ-Al2O3 as a light-absorbing material that generates ultrashort pulses in a wideband wavelength range, which could benefit future research on the metastable state of aluminum-based materials within the field of ultrafast photonics.